2000
DOI: 10.1074/jbc.275.15.11397
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclooxygenase-2 Inhibitor Celecoxib Induces Apoptosis by Blocking Akt Activation in Human Prostate Cancer Cells Independently of Bcl-2

Abstract: This study investigates the apoptotic activity of the cyclooxygenase-2 (COX-2) inhibitor celecoxib in prostate carcinoma cells. COX-2 is constitutively expressed in androgen-responsive LNCaP and androgen-nonresponsive PC-3 cells. Exposure of these cells to celecoxib induces characteristic features of apoptosis, including morphological changes, DNA laddering, and caspase-3 activation, whereas piroxicam, a COX-1-specific inhibitor, displays no appreciable effect on either cancer cell line even after prolonged ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
403
8
8

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 624 publications
(451 citation statements)
references
References 38 publications
32
403
8
8
Order By: Relevance
“…Mitogeninduced activation of PI3-kinase and its downstream target Akt results in phosphorylation of HDM2 on ser166 and 168 and enhanced HDM2 nuclear localization (Mayo and Donner, 2001;Ashcroft et al, 2002). Interestingly, a number of studies have demonstrated that COX-2 inhibitors induce apoptosis by blocking Akt activation in adult carcinomas (Hsu et al, 2000;Arico et al, 2002). However, in this study, we did not observe any early changes in Akt or Akt phosphorylation that could have explained the downregulation of phosphorylated HDM2 mediated by COX inhibitors as early as 2 h. In contrast, we observed dose-dependent reduction of Akt levels after 24 h of COX inhibitor treatment (data not shown) and these late effects may account for the observed sustained downregulation of P-HDM2 up to 48 h by COX inhibitors in neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Mitogeninduced activation of PI3-kinase and its downstream target Akt results in phosphorylation of HDM2 on ser166 and 168 and enhanced HDM2 nuclear localization (Mayo and Donner, 2001;Ashcroft et al, 2002). Interestingly, a number of studies have demonstrated that COX-2 inhibitors induce apoptosis by blocking Akt activation in adult carcinomas (Hsu et al, 2000;Arico et al, 2002). However, in this study, we did not observe any early changes in Akt or Akt phosphorylation that could have explained the downregulation of phosphorylated HDM2 mediated by COX inhibitors as early as 2 h. In contrast, we observed dose-dependent reduction of Akt levels after 24 h of COX inhibitor treatment (data not shown) and these late effects may account for the observed sustained downregulation of P-HDM2 up to 48 h by COX inhibitors in neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…These levels can only be achieved in normal cells by stimulation with growth factors and cytokines [29,70,71]. Active anti-apoptotic functions of COX-2 in cancer cells have been widely reported [72][73][74]. Furthermore, COX-2 is one of the several important genes, which mediate breast cancer metastasis to the lung [75].…”
Section: Cox-2 Inhibition Upregulates Arsenite-induced Apoptosis In Fmentioning
confidence: 99%
“…26 Studies in human prostate cancer cell lines indicate that celecoxib induces apoptosis by blocking Akt and Erk2 activation, through the mitochondrial pathway, independent of COX-2 activity and Bcl-2. 8,29,30 This has led to the design of celecoxib derivatives that optimize the apoptosis-inducing potency, separate from the COX inhibiting activity of celecoxib. 8,[31][32][33] Recent studies with the first and second generation derivatives of celecoxib in the PC-3 human prostate cell line suggests that apoptosis is mediated through the blockade of Akt activation by derivative inhibition of 3-phosphoinositide dependent kinase-1 (PDK1).…”
mentioning
confidence: 99%